Diisodecyl phthalate aggravates thyroid autoimmune injury in thyroglobulin-sensitized rats via endoplasmic reticulum stress-mediated apoptosis and Th17/Treg dysregulation - Zixin Tian; Jianwei Gao; Zhenjie Lu; Keyi Chen; Wanjia Lv; Mei Ye; Yajun Wang; Yanling Sun; Xu Yang; Ping Ma; Yang Wu (Food and Chemical Toxicology, 2026)

PFAS penetrate the bone marrow microenvironment and alter immunometabolic homeostasis - Sijia Gu; Ji Ma; Xiangying Sun; Keyi Li; Mingzhu Wu; Yumeng Shi; Miao Xu; Hongkai Zhu; Hongwen Sun (Environmental Pollution, 2026)

Rapid biodegradation of glyphosate by plant growth-promoting Ochrobactrum sp. Y3: Degradation kinetics, metabolic pathways and environmental bioremediation - Shichen Dai; Chenxi Yan; Mingqiu Liu; Yuxi Sun; Keyi Wang; Guiling Si; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Chemical Engineering, 2026)

Machine learning-driven investigation of key flavor factors in pale lager beer fermentation samples and their evolution mechanisms during fermentation - Jiang Xie; Ruiyang Yin; Xin Yuan; Bofeng Zhong; Liyun Guo; Yumei Song; Wenjing Tian; Yiyu Chen; Keyi Ling; Dongrui Zhao; Baoguo Sun; Jinyuan Sun; et al. (Food Chemistry, 2026)

Pre-existing liver dysfunction modulates di-(2-ethylhexyl) phthalate (DEHP)-associated biological responses through host-microbiome networks - Mingzhu Wu; Shucong Chen; Wencheng Guo; Sijia Gu; Keyi Li; Yumeng Shi; Yu Qian; Yulian Sun; Yarui Liu; Hongkai Zhu (Environmental Pollution, 2026)

Lapatinib Induces Ferroptosis in Cardiomyocytes by Regulating ATF4/GPX4 - Yue Sun; Keyi Jiang; Dan Wang; Chunlei Li; Yuqing You; Long Chen; Wei Chang; Liwei Zhang; Hongqi Feng; Dandan Li; Yilan Li (Cardiovascular Toxicology, 2026)

Crosstalk-free dual-mode electronic skin enabled by selective electrospinning and machine learning-based decoupling - Chu Qin; Qingyin Sun; Chuheng Fu; Keyi Shan; Yuxin Sun; Min Wang (Chemical Engineering Journal, 2026)

Discovery and Optimisation of Novel Bombinin-Derived Peptides from Bombina variegata against Staphylococcus aureus - Jiachen Liu; Keyi Yao; Ruize Sun; Xiaonan Ma; Chengbang Ma; Xiaoling Chen; Yangyang Jiang; Tao Wang; Tianbao Chen; Chris Shaw; Mei Zhou; Lei Wang (Probiotics and Antimicrobial Proteins, 2026)
Amphibian skin-secreted antimicrobial peptides (AMPs) have garnered significant attention for their excellent biological activity and low propensity for drug resistance over the past 40 years. Bombinins and bombinin H, two classes of AMPs isolated from the skin secretions of Bombina species, demonstrate strong antimicrobial activity against broad-spectrum microorganisms. In this study, two novel peptides, bombinin-like peptide 7S and bombinin-H2L, were identified from the toad, Bombina variegata . While both peptides exhibited broad-spectrum antimicrobial activity, they also showed relatively high cytotoxicity. To explore the structure–activity relationship and enhance therapeutic potential, bombinin-H2L, which displayed stronger average antimicrobial activity, was used as a template. With the aid of bioinformatics analysis, a series of bombinin-H2L analogues were designed by increasing the net positive charges and/or adjusting the amphiphilicity of the parent peptide. Among these analogues, [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L demonstrated high therapeutic efficacy and specificity toward clinically isolated, drug-resistant Staphylococcus aureus strains in both in vitro and ex vivo tests. Their notable biosafety profiles, sensitivity to diverse environments, and ability to disrupt biofilms highlight their potential for further development. Additionally, studies on the mechanism of [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L revealed a membrane-targeted antimicrobial mechanism, with its antibacterial function exerted by disrupting the integrity of bacterial membranes. These findings provide valuable insights into structural modifications of bombinin H peptides for enhanced activity, and [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L have the potential as promising candidates for novel antibacterial agents in treated bacterial skin infections.

A high-performance aqueous redox flow battery with long cyclic stability enabled by a novel Janus membrane self-assembled from polyelectrolytes - Quanhu Sun; Keyi Dong; Zefeng Yan; Tian Lv; Yan Tan; Jiaxin Yang; Yu Wang; Weiyang Tang; Tao Chen (Chemical Engineering Journal, 2025)

Insights into the combined effect of ofloxacin and humic substances on sewage sludge anaerobic digestion - Sha Long; Zhixiang Hao; Luyang Sun; Dejiang Ren; Keyi Wang; Huiming Li; Dongbo Wang (Environmental Research, 2025)

Sweat-amplified dermal transfer and combined toxicity of per- and polyfluoroalkyl substances and organophosphate esters mixtures in children's textiles - Keyi Li; Xiangying Sun; Yu Qian; Wencheng Guo; Yumeng Shi; Mingzhu Wu; Zhipeng Cheng; Hongzhi Zhao; Yarui Liu; Hongkai Zhu (Science of The Total Environment, 2025)

A hydroxyl coumarin-chalcone-based fluorescent probe for sensing copper ions in plant and living cells - Keyi Li; Yan Huang; Yatong Sun; Yiping Zhang; Yan Zhang; Baosheng Ren; Duxia Cao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Impacts of biodegradable microplastics on rhizosphere bacterial communities of Arabidopsis thaliana: Insights into root hair-dependent colonization - Keyi Chen; Zhihui Jin; Qing Zhu; Xiaodie Hu; Sijia Tian; Yulin Wang; Yaru Sun; Ming Yuan; Huaiying Yao (Environmental Research, 2025)

Untargeted metabolomics and machine learning unveil the exposome and metabolism linked with the risk of early pregnancy loss - Yixuan Shi; Keyi Li; Ran Ding; Xiaoying Li; Zhipeng Cheng; Jialan Liu; Shaoxia Liu; Hongkai Zhu; Hongwen Sun (Journal of Hazardous Materials, 2025)

Non-degradable microplastic promote microbial colonization: A meta-analysis comparing the effects of microplastic properties and environmental factors - Zhihui Jin; Keyi Chen; Qing Zhu; Xiaodie Hu; Sijia Tian; Airong Xiang; Yaru Sun; Ming Yuan; Huaiying Yao (Environmental Research, 2025)

Reconstruction of cobalt atoms in ZIF-67 and in-situ growth of carbon nanotubes at low temperature for High-Performance strain sensors - Xiao Li; Tian Lv; Keyi Dong; Jiaxin Yang; Weiyang Tang; Zilin Chen; Yu Duan; Quanhu Sun; Dongmei Zhai; Tao Chen (Chemical Engineering Journal, 2025)

A microphase-separation ionogel electrolyte for highly stretchable all-solid-state supercapacitors - Weiyang Tang; Keyi Dong; Zilin Chen; Yu Duan; Quanhu Sun; Xiao Li; Dongmei Zhai; Tian Lv; Tao Chen (Chemical Engineering Journal, 2024)

Game changer for anaerobic fermentation of paper mulberry: Sucrose-loaded biochar enhancing microbial communities and lactic acid fermentation - Jingwen Cao; Hongzhang Zhou; Xuekai Wang; Yang Wang; Yu Li; Stephen Joseph; Xiaorong Wang; Mengyao Sun; Keyi Zhang; Yanli Lin; Gang Xu; Kuikui Ni; et al. (Bioresource Technology, 2024)

Realizing reasonable redistribution of platform capacity through valence structure optimization for low strain Na3MnZr(PO4)3 cathode material - Mengting Deng; Yulei Sui; Kexin Rao; Yian Wang; Wenbin Fei; Keyi Sun; Zonglin Yang; Xiaoping Zhang; Ling Wu (Chemical Engineering Journal, 2024)

Rational design of bilayer heterogeneous poly(ionic liquid)s electrolytes for high-performance flexible supercapacitors with ultraslow self-discharge rate - Keyi Dong; Weiyang Tang; Quanhu Sun; Zilin Chen; Xiao Li; Dongmei Zhai; Zefeng Yan; Jiaxin Yang; Tian Lv; Tao Chen (Chemical Engineering Journal, 2024)

A novel bimetallic-polyanion Na4Fe2.82Ni0.18(PO4)2P2O7 cathode with superior rate performance and long cycle-life for sodium-ion batteries - Wenbin Fei; Yian Wang; Xiaoping Zhang; Jiuxiang Zhang; Shengxing Lu; Kexin Rao; Keyi Sun; Mengting Deng; Yuxuan Liu; Qingqiang Li; Ling Wu; Yulei Sui (Chemical Engineering Journal, 2024)

Geochemical and U-Pb isotopic insights into uranium (U) enrichment in the soil around a nuclear fuel element plant, in Southwest China - Xin Cheng; Jianing Sun; Kai Ling; Keyi Zhong; Bolin Shao; Lan Li; Shanshan Zhao; Yi Huang; Hao Song; Bo Cheng (Ore and Energy Resource Geology, 2024)

Degradation mechanism analysis of substrate and microporous layer of gas diffusion layer in proton exchange membrane fuel cell - Keyi Xu; Qian Di; Fengman Sun; Ming Chen; Haijaing Wang (Fuel, 2024)

Large-scale surface water-groundwater origins and connectivity in the Ordos Basin, China: Insight from hydrogen and oxygen isotopes - Shen Qu; Chenyu Wang; Nuan Yang; Limin Duan; Ruihong Yu; Keyi Zhang; Muhan Li; Pengfei Sun (Environmental Research, 2023)

A novel hydrogel electrolyte for all-climate high-performance flexible zinc-ion hybrid capacitors within temperature range from −50 to 100 °C - Yu Duan; Tian Lv; Keyi Dong; Feng Zheng; Xiao Li; Yunlong Qi; Zilin Chen; Weiyang Tang; Quanhu Sun; Shaokui Cao; Tao Chen (Chemical Engineering Journal, 2023)

Microplastic pollution destabilized the osmoregulatory metabolism but did not affect intestinal microbial biodiversity of earthworms in soil - Ronggui Tang; Minshen Ying; Yongming Luo; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Tao Sun; Yutao Cao; Zhihan Diao; Yuxin Zhang; Yichen Lian; Keyi Chen; Yan Yan; et al. (Environmental Pollution, 2023)

Nanoplastics induce molecular toxicity in earthworm: Integrated multi-omics, morphological, and intestinal microorganism analyses - Ronggui Tang; Dong Zhu; Yongming Luo; Defu He; Haibo Zhang; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Keyi Chen; Yan Yan; Xinghang Lu; Minshen Ying; Tao Sun; et al. (Journal of Hazardous Materials, 2023)